REPUTATION TRANSMISSION WITHOUT BENEFIT TO THE REPORTER: A BEHAVIORAL UNDERPINNING OF MARKETS IN EXPERIMENTAL FOCUS. (10th August 2017) - Kamei, Kenju; Putterman, Louis
Abstract : Reputation is a commonly cited check on opportunism, but it is often unclear what motivates an agent to report another's behavior when it is easy for the aggrieved individual to move on. In a sharply focused laboratory experiment, we find that many cooperators pay to report a defecting partner without the possibility of pecuniary benefit when this has the potential to deprive the latter of future gains and to help his next partner. We illustrate how a social preference can explain such costly reporting, and also discuss evidence for a role of emotions. ( JEL C91, D03, D63)